2009
DOI: 10.1128/iai.00238-09
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptors 2 and 4 Contribute to Sepsis-Induced Depletion of Spleen Dendritic Cells

Abstract: Depletion of dendritic cells (DC) in secondary lymphoid organs is a hallmark of sepsis-induced immune dysfunction. In this setting, we investigated if؊/؊ TLR4 ؊/؊ mice. Accordingly, apoptosis of spleen DC was increased in septic wild-type mice and inhibited in knockout mice. In addition we characterized the functional features of spleen DC obtained from septic mice. As shown by increased expression of major histocompatibility complex class II and CD86, polymicrobial sepsis induced maturation of DC, with subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 31 publications
3
33
0
Order By: Relevance
“…Because of its potent Ag presentation properties, DCs are required for induction of immune responses at the onset of infection and quantitative, and functional loss of DCs has been attributed to severity of infectious diseases. 56,57 In this context, our studies raise the possibility that nonsteroidal anti-inflammatory agents inhibiting PGE 2 biosynthesis, particularly when taken over extended periods of time, may exacerbate disease as a consequence of reduced DC generation. In addition, several experimental and clinical studies support the use of DC vaccines 58 ; however, current DC vaccines are not optimal for the treatment of human diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its potent Ag presentation properties, DCs are required for induction of immune responses at the onset of infection and quantitative, and functional loss of DCs has been attributed to severity of infectious diseases. 56,57 In this context, our studies raise the possibility that nonsteroidal anti-inflammatory agents inhibiting PGE 2 biosynthesis, particularly when taken over extended periods of time, may exacerbate disease as a consequence of reduced DC generation. In addition, several experimental and clinical studies support the use of DC vaccines 58 ; however, current DC vaccines are not optimal for the treatment of human diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the sublethal sepsis enhanced the risk for secondary infections (Fig. 1F) that could be restored through application of naive DC (25). The mechanisms underlying the sustained reduction of the number of splenic DC in post-septic mice have not been investigated so far.…”
Section: Discussionmentioning
confidence: 99%
“…Potential prognostic value of the selective depletion of spleen DCs, which are essential to develop an efficient immune response (37), has been reported for patients with sepsis (20) and in animal models of sepsis (32). We have recently shown that TLR2 and TLR4 signaling is involved in the mechanisms leading to depletion of spleen DCs following polymicrobial sepsis (31). Analysis of the expression of proteins involved in TLR signaling in our microarray analysis reveals that only the factor Tollip is downregulated in rel Ϫ/Ϫ mice after CLP (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…DCs link innate immunity and adaptive immunity and are critical in mounting and coordinating host immune responses against infection. Moreover, the importance of DCs in both the early and late phases of sepsis has been established (4,31), with these cells having been reported to be required for survival of polymicrobial sepsis (37). In wt mice, a selective depletion of the spleen lymphoid DC subset CD11c ϩ CD8␣ ϩ was found at day 1, followed by a full replenishment at day 7 after CLP.…”
Section: Sublethal Polymicrobial Sepsis Induces Increased Mortality Imentioning
confidence: 99%